TEACHER PROFESSIONAL DEVELOPMENT: PREPARING GRADUATE STUDENTS TO HAVE 4C SKILLS IN FACING INDUSTRIAL REVOLUTION 4.0 - Perdani, Yella Dezas; Gita Rahmi; Widyasari, Yessi (Bina Nusantara University, 2025)
There were several problems faced by the teachers in the community, including how to prepare the students to face the Industrial Revolution 4.0. Hence, the community activity aimed at informing the teachers to prepare their students with industrial revolution 4.0 skills including critical thinking, problem-solving, communication, collaboration, creativity, and innovation skills to face the industrial revolution 4.0. The research used community-based research to arrange the activity from the beginning until the end. Qualitative research was also used in the research design. There were 37 teachers as the participants in the research, and the data collection technique used was observation. There were three main findings of the research. First, it was found that the participants were engaged in the activity. Second, the teachers also discussed each other during the activity. Third, the teacher gave good feedback on the activity, including the materials and presenters. The findings indicated that the activity significantly enhanced the teacher engagement, collaboration, and feedback during the activity that emphasized the materials importance in enhancing professional development and equipping them to prepare their students in facing industrial revolution 4.0 era.